Flexural strength and modulus of autopolimerized poly (methyl methacrylate) with nanosilica - Balos Sebastian; Pilić Branka; Petrović Đorđe; Petronijević Branislava; Šarčev Ivan (Vojnosanitetski Pregled)
Background/Aim. Autopolymerized, or cold polymerized poly(methyl methacrylate) class of materials have a lower mechanical properties compared to hot polymerized poly(methyl methacrylate), due to a limited time of mixing before the polymerization process begins. The aim of this study was to test the effect of different relatively low nanosilica contents, in improving mechanical properties of the cold polymerized poly(methyl methacrylate). Methods. A commercially available autopolymerized poly(methyl methacrylate) denture reline resin methyl methacrylate liquid component was mixed with 7 nm after treated hydrophobic fumed silica and subsequently mixed with poly(methyl methacrylate) powder. Three nanosilica loadings were used: 0.05%, 0.2% and 1.5%. Flexural modulus and strength were tested, with one way ANOVA followed by Tukey’s test. Furthermore, zeta potential, differential scanning calorimetry, scaning electrone microscopy and energy dispersive X-ray analyses were performed. Results. Flexural modulus and strength of poly(methyl methacrylate) based nanocomposites were statistically significantly increased by the addition of 0.05% nano-SiO2. The increase in nanosilica content up to 1.5% does not contribute to mechanical properties tested, but quite contrary. The main reason was agglomeration, that occurred before mixing of the liquid and powder component and was proved by zeta potential measurement, and after mixing, proved by scanning electrone microscopy and energy dispersive x-ray analyses. Conclusions. Addition of 7 nm 0.05% SiO2 is the most effective in increasing flexural modulus and strength of autopolimerized poly(methyl methacrylate).